VOLATILITÉ DU TAUX DE CHANGE ET LES INVESTISSEMENTS DIRECTS ETRANGERS EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO DE 1985 À 2020 - Marcel, SENGA PESSE (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This research aimed to assess the existence of a link between exchange rate volatility and FDI (Foreign Direct Investment) in the Democratic Republic of Congo. To do this, it used the Autoregressive Distributed Lag model, using annual data from 1985 to 2020, a period of 36 years. The results reveal that in the short term, exchange rate volatility has a positive and statistically insignificant effect on FDI. However, in the long term, the effect of exchange rate volatility becomes negative and statistically insignificant on FDI in the DRC during the period under review.